Analisis Pengaruh Kepuasan Pelanggan, Kepercayaan dan Citra Merek Terhadap Loyalitas Pelanggan Produk Buttonscarves Di Kota Surabaya - Prastyaningrum, RA. Bulan Anugrah; Samsudin, Acep (Universitas Galuh, 2024)
The main objective of this study is to determine how consumer loyalty to Buttonscarves products in Surabaya is influenced by factors such as brand image, trust, and customer satisfaction. 204 people were required to complete the survey. The data in this study was analyzed using multiple linear analysis, a sampling approach known as purposive sampling. Primary data, or information obtained directly from the research item itself, was used in this study. According to the authors of the study, there is a significant relationship between satisfaction, trust, and brand image and customer loyalty. Trust and brand image are two factors that significantly influence customer loyalty; however, customer satisfaction has no effect on loyalty.